ZORA 158: Oblačilno izrazje pri Sveti Trojici v Slovenskih goricah - Koletnik, Mihaela; Gungl, Benedikta (University of Maribor Press, 2025)
ZORA 158: Clothing Terminology in Sveta Trojica in Slovenske gorice. The monograph presents the results of research on the local dialectal clothing terminology in Sveta Trojica in Slovenske Gorice. Based on the phonological traits observed – especially the consistent preservation of vowel length in historically short stressed vowels, along with distinctive markers of the eastern Slovene Pannonian dialect area – we can confidently classify the Sveta Trojica dialect as part of the Slovenske Gorice dialect within the broader Pannonian group. The central part of the monograph represents the first extensive contribution to the understanding of dialectal clothing terminology in Sveta Trojica. It documents the traditional rural attire of men, women, and children during the second half of the 20th century, as well as garments worn on special occasions. The description draws on oral narratives from local female informants, photographic evidence, and experiential knowledge. The clothing terminology specific to Sveta Trojica, as presented and analyzed in this monograph, was obtained through structured interviews with the informants. These terms are categorized into seven semantic fields and supplemented with selected illustrative material (304 pictures). The final compilation includes 736 dictionary entries, arranged in alphabetical order. Lexems are analyzed in terms of its word-formation characteristics and origin. This approach sheds light on the phenomenon of foreign linguistic elements entering the dialect. The terms are also compared with entries found in lexicographic works that cover the standard language – specifically Pleteršnik’s Dictionary (1894–1895) and the Dictionary of Standard Slovene2 – in order to trace the historical presence of individual words in both dialect and standard language, determine their prevalence, and highlight potential semantic differences.